Bacterial Cellulose - Barud, Hernane S. [UNESP]; Gutierrez, Junkal; Lustri, Wilton R.; Peres, Maristela F.S. [UNESP]; Ribeiro, Sidney J.L. [UNESP]; Saska, Sybele [UNESP]; Tercjak, Agniezska (Wiley, 2016)
Bacterial Cellulose is produced extracellularly, in the form of nanofibers, by various bacteria genera, such as Gluconacetobacter, Agrobacterium, Aerobacter, Achromobacter, Azotobacter, Rhizobium, Sarcina, and Salmonella. Current methods of BC production include static culture, submerged fermentation through aerated or agitated cultivation and airlift bioreactors. BC membrane in a dried or never dried state has been extensively used as dressings for wound healing. Despite being natural wound dressings, bacterial cellulose-based dressings themselves present no antimicrobial activity to help in preventing wound infection. In order to achieve antimicrobial properties, BC membranes have been associated with different antimicrobial agents like silver nanoparticles, potassium sorbate, propolis, clays or chitosan. Besides medical applications and healthcare, self-sterilizing textiles, water purification and food packages are areas where BC membranes presenting antimicrobial activities could find application. Tissue engineering has achieved great progress in the development of scaffolds for repair or replacement of damaged tissues or organs.
Keywords: Airlift bioreactors; Antimicrobial activities; Antimicrobial agents; Bacterial cellulose; Self-sterilizing textiles; Silver nanoparticles; Submerged fermentation; Tissue engineering; Wound healing